Salinomycin as a drug for targeting human cancer stem cells - Naujokat, Cord; Steinhart, Roman (Journal of biomedicine and biotechnology, 2012)
Cancer stem cells (CSCs) represent a subpopulation of tumor cells that possess self-renewal and tumor initiation capacity and the ability to give rise to the heterogenous lineages of malignant cells that comprise a tumor. CSCs possess multiple intrinsic mechanisms of resistance to chemotherapeutic drugs, novel tumor-targeted drugs, and radiation therapy, allowing them to survive standard cancer therapies and to initiate tumor recurrence and metastasis. Various molecular complexes and pathways that confer resistance and survival of CSCs, including expression of ATP-binding cassette (ABC) drug transporters, activation of the Wnt/β-catenin, Hedgehog, Notch and PI3K/Akt/mTOR signaling pathways, and acquisition of epithelial-mesenchymal transition (EMT), have been identified recently. Salinomycin, a polyether ionophore antibiotic isolated from Streptomyces albus, has been shown to kill CSCs in different types of human cancers, most likely by interfering with ABC drug transporters, the Wnt/β-catenin signaling pathway, and other CSC pathways. Promising results from preclinical trials in human xenograft mice and a few clinical pilote studies reveal that salinomycin is able to effectively eliminate CSCs and to induce partial clinical regression of heavily pretreated and therapy-resistant cancers. The ability of salinomycin to kill both CSCs and therapy-resistant cancer cells may define the compound as a novel and an effective anticancer drug.